Improving nelarabine efficacy in T cell acute lymphoblastic leukemia by targeting aberrant PI3K/AKT/mTOR signaling pathway. Issue 1 (December 2016) - Lonetti, Annalisa; Cappellini, Alessandra; Bertaina, Alice; Locatelli, Franco; Pession, Andrea; Buontempo, Francesca; Evangelisti, Camilla; Evangelisti, Cecilia; Orsini, Ester; Zambonin, Laura; Neri, Luca; Martelli, Alberto; et al.
Abstract Background Although in recent years, the introduction of novel chemotherapy protocols has improved the outcome of T cell acute lymphoblastic leukemia (T-ALL) patients, refractory and/or relapsing disease remains a foremost concern. In this context, a major contribution was provided by the introduction of the nucleoside analog nelarabine, approved for salvage treatment of T-ALL patients with refractory/relapsed disease. However, nelarabine could induce a life-threatening, dose-dependent neurotoxicity. To improve nelarabine efficacy, we have analyzed its molecular targets, testing selective inhibitors of such targets in combination with nelarabine. Methods The effectiveness of nelarabine as single agent or in combination with PI3K, Bcl2, and MEK inhibitors was evaluated on human T-ALL cell lines and primary T-ALL refractory/relapsed lymphoblasts. The efficacy of signal modulators in terms of cytotoxicity, induction of apoptosis, and changes in gene and protein expression was assessed by flow cytometry, western blotting, and quantitative real-time PCR in T-ALL settings. Results Treatment with nelarabine as a single agent identified two groups of T-ALL cell lines, one sensitive and one resistant to the drug. Whereas sensitive T-ALL cells showed a significant increase of apoptosis and a strong down-modulation of PI3K signaling, resistant T-ALL cells showed a hyperactivation of AKT and MEK/ERK1/2 signaling pathways, not caused by differences in the expression of nelarabine transporters or metabolic activators. We then studied the combination of nelarabine with the PI3K inhibitors (both pan and dual γ/δ inhibitors), with the Bcl2 specific inhibitor ABT199, and with the MEK inhibitor trametinib on both T-ALL cell lines and patient samples at relapse, which displayed constitutive activation of PI3K signaling and resistance to nelarabine alone. The combination with the pan PI3K inhibitor ZSTK-474 was the most effective in inhibiting the growth of T-ALL cells and was synergistic in decreasing cell survival and inducing apoptosis in nelarabine-resistant T-ALL cells. The drug combination caused AKT dephosphorylation and a downregulation of Bcl2, while nelarabine alone induced an increase in p-AKT and Bcl2 signaling in the resistant T-ALL cells and relapsed patient samples. Conclusions These findings indicate that nelarabine in combination with PI3K inhibitors may be a promising therapeutic strategy for the treatment of T-ALL relapsed patients.